Tension-tension fatigue behavior of unidirectional SiC/Si3N4 composite with strong and weak interface bonding at room temperature. Issue 12 (15th August 2017) - Li, L.B.; Reynaud, P.; Fantozzi, G.
Abstract: In this paper, the tension-tension fatigue behavior of unidirectional SiC/Si3 N4 ceramic-matrix composite with strong and weak interface bonding at room temperature has been investigated using a micromechanical approach. The hysteresis loops models considering different interface slip cases have been developed to establish the relationships between fatigue hysteresis loops, hysteresis dissipated energy, hysteresis modulus, and the interface shear stress. The damage evolution process under tension-tension fatigue loading has been analyzed using hysteresis loops. By comparing experimental fatigue hysteresis dissipated energy with theoretical computational values, the interface shear stresses of SiC/Si3 N4 composite with weak and strong interface bonding were obtained for different cycle numbers. The fatigue life S‒N curves and broken fibers fraction versus cycle number curves corresponding to different fatigue peak stresses have been predicted. For SiC/Si3 N4 with strong interface bonding, the fatigue limit stress approaches to 75% tensile strength, which is much higher than that of composite with weak interface bonding, i.e., 58% tensile strength, due to the higher interface shear stress degradation rate for weak bonding interface.